Rabindra Nath Tagore's Mysticism and Humanism in Poetry: Exploring the Nexus of Mysticism and Humanism in Rabindra Nath Tagore's Poetry (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Mysticism is defined as a collection of diverse practices, discourses, texts, institutions,traditions, and experiences directed at human transformation, as defined by various traditions.Mysticism is a phrase that encompasses anything that has to do with God. Tagore entered the domainof mysticism because of his passion for nature and God, according to an analysis of his words andconcepts. As a result, Rabindra nath‘s Gitanjali is better described as Nature Mysticism rather thanSoul or God. Only enlightened saints and poets such as Kalidasa and Auribindo are capable ofattaining mysticism. Humanism is a phrase with a long and complicated history, as well as an unusuallybroad range of meanings and applications. Readers have been baffled by how various authors haveused it in various ways. Humanism was a cultural, literary, scientific, and intellectual movement thatadvocated for the study of humanities, ancient Greek and Roman languages, literature, and history. Inwriting, study, and other aspects of life, humanist intellectuals modeled themselves after ancientauthors.